2014
DOI: 10.1186/s12875-014-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary care treatment guidelines for skin infections in Europe: congruence with antimicrobial resistance found in commensal Staphylococcus aureusin the community

Abstract: BackgroundOver 90% of antibiotics for human use in Europe are prescribed in primary care. We assessed the congruence between primary care treatment guidelines for skin infections and commensal Staphylococcus aureus (S. aureus) antimicrobial resistance levels in community-dwelling persons.MethodsThe prevalence of antimicrobial resistance in S. aureus was analysed by taking nose swabs from healthy primary care patients in nine European countries (total N = 32,032). Primary care treatment guidelines for bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…However, in around one of six participants no antimicrobial resistant CoNS isolates were found. The highest prevalence of antimicrobial resistance was towards erythromycin, fusidic acid, tetracycline and clindamycin, all antimicrobial agents commonly prescribed in primary health care to treat respiratory tract and skin infections (16). A recent Portuguese study on community CoNS reported overall higher prevalence of resistance than in our Norwegian isolates, and showed a higher prevalence of resistance towards agents commonly prescribed antibiotics in primary care (12).…”
Section: Discussionmentioning
confidence: 58%
“…However, in around one of six participants no antimicrobial resistant CoNS isolates were found. The highest prevalence of antimicrobial resistance was towards erythromycin, fusidic acid, tetracycline and clindamycin, all antimicrobial agents commonly prescribed in primary health care to treat respiratory tract and skin infections (16). A recent Portuguese study on community CoNS reported overall higher prevalence of resistance than in our Norwegian isolates, and showed a higher prevalence of resistance towards agents commonly prescribed antibiotics in primary care (12).…”
Section: Discussionmentioning
confidence: 58%
“…As antibiotic resistance against classical antibiotics is rapidly emerging, alternative treatment options are desperately needed [456]. Staphefekt SA.100 is a recombinant phage endolysin for topical skin application that specifically binds to the cell wall of S. aureus and cleaves bonds in the peptidoglycan wall, resulting in bacterial cell death [7].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is one of the most important serious opportunistic human pathogens involved in nosocomial infections [1,2]. Resistance to methicillin primarily derives from acquisition of the mecA gene, which encodes a modified penicillin‐binding protein (PBP2a) with low affinity for β‐lactams [2].…”
Section: Introductionmentioning
confidence: 99%